Frequency and Distribution of Gram Negative Bacteria among Hospital and Community Acquired UTI Patients (Bangladesh Journal of Infectious Diseases, 2015)
Background: Gram negative bacteria create a great problem during the treatment of urinary tract infection patients. Objective: This study was undertaken to determine the frequency and distribution of Gram negative bacteria among the UTI patients. Methodology: This cross sectional study was carried out in the Department of Microbiology at Sir Salimullah Medical College, Dhaka from June 2007 to May 2008 for a period of 1(one) year. All the patients presented with the clinically suspected UTI at any age with both sexes were selected as study population. Patients who were hospitalized for at least 2 days or more received different antibiotics were designated as hospital acquired UTI; on the other hand patients who were attended in OPD for the first time were considered as community acquired UTI patients. All urine samples were inoculated in Blood agar and MacConkeys agar media. Gram negative bacteria were isolated and identified by colony morphology, Gram staining and biochemical tests. Result: A total of 220 urine samples were collected from patients suspected to urinary tract infections of which 116 samples were from hospitalized patients and 104 samples were from community patients. Among 220 samples, 132(60.0%) Gram negative bacteria were isolated of which 88(66.7%) isolates were from hospitalized acquired UTI and 44(33.3%) bacteria were isolated from community acquired UTI patients. The difference was statistically significant (p=0.0001). In hospitalized patients out of 88(75.9%) isolated Gram negative bacteria, 67(76.1%) isolates were Escherichia coli, 10(11.4%) isolates were Klebsiella species, 5(5.7%) isolates were Proteus species and 6(6.8%) isolates were Pseudomonas species. Among the isolated bacteria 44(42.3%) bacterial isolates were from community patients of which 36(81.8%) isolates were Escherichia coli, 4(9.1 %) isolates were Klebsiella species, 2(4.5%) isolates were Proteus species and 2(4.5%) bacteria were Pseudomonas species. Conclusion: In the present study, it was observed that considerable numbers of Gram negative bacteria were detected from urinary tract infection cases.Bangladesh Journal of Infectious Diseases 2014;1(2):24-26